Effect of play‐based summer break exercise on cardiovascular function in adolescents. (8th November 2012) - Meucci, Marco; Curry, Chelsea D; Baldari, Carlo; Guidetti, Laura; Cook, Carol; Collier, Scott R
Abstract Aim To compare the effects of 4 and 8 weeks of play‐based, supervised exercise during summer break versus an unsupervised break on cardiovascular function in adolescent children. Methods Twenty‐two subjects were divided into a 4‐week exercise group (age 10.1 ± 1.3 years), an 8‐week exercise group (age 9.4 ± 1.7 years) or a control group (age 10.0 ± 1.3 years). The activity groups participated in a supervised summer camp for 6 h/day, 5 days/week including a discontinuous play‐based physical activity program and a healthy lifestyle, while the control group were told to keep their regular summer break routines. Anthropometrics, pulse wave velocity, augmentation index, blood pressure and peak oxygen consumption were evaluated before and after the intervention. Results Normalized augmentation index (75 beats/min) significantly decreased after 4 and 8 weeks in the active groups (p = 0.04) while pulse wave velocity showed no significant changes in all groups. Mean arterial pressure decreased (p = 0.003) and peak oxygen consumption increased (p = 0.001) significantly in the 8 week group. Conclusion These data suggest that 8 weeks of supervised play‐based activity yield several cardio‐beneficial results in adolescents, which may act as a clinical prophylaxis throughout their lifetime.